2021
DOI: 10.1021/acsami.0c19451
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Si-Rich Interfaces by Radiation-Induced Diffusion and Microsegregation in CrN/ZrN Nanolayer Coating

Abstract: A combination of coating deposition and consequent ion implantation could be beneficial in wear-resistant antifriction surface design and modification. In the present paper, the effects of low-energy 60 keV Si-ion implantation on multinanolayered CrN/ZrN grown on a stainless-steel substrate have been investigated. Complementary experimental (X-ray diffraction, high-resolution transmission electron microscopy, energy-dispersive spectroscopy, secondary ion mass spectrometry) and theoretical (first-principles) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 64 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…In the case of MoCN coating, a higher wear depth (∼2150 nm) with the irregular curve was obtained, revealing the lower wear resistance of ∼7.3 × 10 –5 mm 3 /N m, and these possible wear scars are developed due to the trapping of third-body wear particles at the interacting interfaces. These particles are hard enough to produce deep scratches on the coating surface representing abrasive nature because of the reduced mechanical properties . The friction (0.64 ± 0.08) and wear rate (9.6 × 10 –4 mm 3 /N m) were found to be significantly higher for the bare 316L SS substrates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of MoCN coating, a higher wear depth (∼2150 nm) with the irregular curve was obtained, revealing the lower wear resistance of ∼7.3 × 10 –5 mm 3 /N m, and these possible wear scars are developed due to the trapping of third-body wear particles at the interacting interfaces. These particles are hard enough to produce deep scratches on the coating surface representing abrasive nature because of the reduced mechanical properties . The friction (0.64 ± 0.08) and wear rate (9.6 × 10 –4 mm 3 /N m) were found to be significantly higher for the bare 316L SS substrates.…”
Section: Resultsmentioning
confidence: 99%
“…These particles are hard enough to produce deep scratches on the coating surface representing abrasive nature because of the reduced mechanical properties. 35 The friction (0.64 ± 0.08) and wear rate (9.6 × 10 −4 mm 3 /N m) were found to be significantly higher for the bare 316L SS substrates. Survey spectra (Figure 5e) disclosed that the primary elements (Mo and C) from the coating, as well as reactive O from the atmosphere and mild transfer of the element Fe from the sliding counterbody were also observed in the MoC wear track.…”
Section: Resultsmentioning
confidence: 99%
“…If these deposits had good adhesion with the substrate, they could act as protectors, but in this case, part of the product is easily lifted, which may indicate that they could be mostly hydroxides. Similarly, the samples that have been coated with the sol-gel are shown in backscattered electrons (BSE) in Figure 7 [ 41 , 42 ]. In comparison, no cracks or corrosion products such as oxides/hydroxides appear in the sample without protective coating from the crosssection view (sample AL of Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…For many decades monolayer nitrides, such as TiN, ZrN, and CrN, have been used for tribological applications. However, numerous studies have demonstrated that alternating deposition of binary nitride layers produces multilayer coatings with superior properties, i.e., TiN/ZrN, TiN/CrN, CrN/ZrN, MoN/CrN, and TiN/MoN [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. That resulted in the widespread interest in multilayer architecture since it provides high hardness, wear resistance, and thermal stability.…”
Section: Introductionmentioning
confidence: 99%